Pengaruh Regulasi Diri terhadap Kenakalan Remaja - Putri Lailatun Nuzul; Abdul Amin (Ilmu Psikologi Universitas Yudharta Pasuruan, 2021)
This study aims to determine the effect of self-regulation on juvenile delinquency. The research was conducted in Warungdowo Village, Pohjentrek District, Pasuruan Regency. The population of this study amounted to 200 adolescents and the sampling technique used simple random sampling, and get a sample of 132 adolescents. The data collection in this study used the self-regulation scale and juvenile delinquency scale. Based on the results of the validity test of the juvenile delinquency scale, it has a validity coefficient that ranges from 0.305 to 0.482 and a reliability coefficient of 0.877. The self-regulation scale has a validity coefficient that ranges from 0.303 to 0.636 and a reliability coefficient of 0.980. The data obtained were analyzed using simple regression analysis techniques. Based on the results of the analysis, the value of rxy = -0.241 > r tab 1% (0.210), it means that there is a negative correlation between self-regulation and juvenile delinquency. From the calculation results also obtained the Freg value of 130.00 > F table 1% (3.91). This means that there is an influence of self-regulation on juvenile delinquency.